Clinical and biological relevance of CREB3L1 in Philadelphia chromosome-negative myeloproliferative neoplasms. (August 2022) - De Marchi, Federico; Okuda, Maho; Morishita, Soji; Imai, Misa; Baba, Terumi; Horino, Mei; Mori, Yosuke; Furuya, Chiho; Ogata, Satoko; Yang, Yinjie; Ando, Jun; Ando, Miki; et al.
Abstract: Cyclic AMP-response element-binding protein 3-like 1 (CREB3L1) is a gene involved in the unfolded protein response (UPR). Recently, we demonstrated that CREB3L1 is specifically overexpressed in the platelets of patients with Philadelphia chromosome-negative myeloproliferative neoplasms (MPNs). In this study, we aimed to show the clinical and biological relevance of CREB3L1 in these hematological diseases. Overexpression of CREB3L1 was specific to platelets in MPNs and associated with a higher risk of thrombosis and fibrotic transformation in essential thrombocythemia (ET) and polycythemia vera (PV) cases, respectively. Furthermore, we found that UPR genes were downregulated in platelets of patients with ET and PV, which were more pronounced in patients harboring the JAK2 V617F mutation. However, CREB3L1 overexpression does not alter UPR gene expression or cell proliferation in UT-7/TPO/CALRm cells exogenously expressing mutated calreticulin and HEL cells harboring endogenous JAK2 V617F. Furthermore, CREB3L1 overexpression did not modulate sensitivity to endoplasmic reticulum stress in these cell lines. Taken together, our data show 1) a potential role of CREB3L1 expression in platelets as a new marker of high-risk MPNs and 2) an association between CREB3L1 overexpression and UPR gene downregulation in these patients' platelets, with CREB3L1 not altering UPR in our in vitro models and possibly further in vivo mechanisms being involved. Highlights: CREB3L1 expression is specific for MPN platelets. CREB3L1 expression is associated with higher risk ET and PV. UPR genes are downregulated in ET and PV platelets. UPR genes expression is independent of CREB3L1 expression in cell line models. CREB3L1 does not alter cell proliferation/ER stress sensitivity in cell line models.